PLANT ORNAMENT IN POTTERY ART OF UZBEKISTAN (Web of Teachers: Inderscience Research, 2025)
This article examines the artistic features of the plant ornament of traditional ceramics of Uzbekistan. It also analyzes the historical development of traditional ceramics of Uzbekistan.